Oncolytic Viruses for Cancer Therapy: Overcoming the Obstacles - Yaohe Wang; Han Hsi Wong; Nicholas R. Lemoine (Viruses, 2010)
Targeted therapy of cancer using oncolytic viruses has generated much interest over the past few years in the light of the limited efficacy and side effects of standard cancer therapeutics for advanced disease. In 2006, the world witnessed the first government-approved oncolytic virus for the treatment of head and neck cancer. It has been known for many years that viruses have the ability to replicate in and lyse cancer cells. Although encouraging results have been demonstrated in vitro and in animal models, most oncolytic viruses have failed to impress in the clinical setting. The explanation is multifactorial, determined by the complex interactions between the tumor and its microenvironment, the virus, and the host immune response. This review focuses on discussion of the obstacles that oncolytic virotherapy faces and recent advances made to overcome them, with particular reference to adenoviruses.